2017
DOI: 10.1208/s12248-017-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Advantageous Solubility-Permeability Interplay When Using Amorphous Solid Dispersion (ASD) Formulation for the BCS Class IV P-gp Substrate Rifaximin: Simultaneous Increase of Both the Solubility and the Permeability

Abstract: Rifaximin is a BCS class IV (low-solubility, low-permeability) drug and also a P-gp substrate. The aims of this work were to assess the efficiency of different rifaximin amorphous solid dispersion (ASDs) formulations in achieving and maintaining supersaturation and to investigate the consequent solubility-permeability interplay. Spray-dried rifaximin ASDs were prepared with different hydrophilic polymers and their ability to achieve and maintain supersaturation was assessed. Then, rifaximin's apparent intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…12 Therefore, if GLPS can be maintained in vivo, it may also represent the concentrations that will help overcome other barriers that might be present (e.g., efflux) or represent concentrations that will be available to be taken up by intestinal uptake transporters. 11 Therefore, it is imperative to appropriately account for the maximum available concentrations that can be reached in the GI tract. For venetoclax, the amorphous solubility in pure aqueous conditions was the most relevant measurement to use in the PBPK model for this particular type of clinical/commercial formulation (ASD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Therefore, if GLPS can be maintained in vivo, it may also represent the concentrations that will help overcome other barriers that might be present (e.g., efflux) or represent concentrations that will be available to be taken up by intestinal uptake transporters. 11 Therefore, it is imperative to appropriately account for the maximum available concentrations that can be reached in the GI tract. For venetoclax, the amorphous solubility in pure aqueous conditions was the most relevant measurement to use in the PBPK model for this particular type of clinical/commercial formulation (ASD).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The increased solution concentration of the drug provided via its amorphous solubility has been demonstrated to drive flux through epithelial barriers present in the gastrointestinal (GI) tract, typically resulting in higher overall exposures. 11,12 A key factor limiting the utilization of ASDs is physical stability and the potential for crystallization of the drug upon generation of the metastable, supersaturated state in aqueous solution. Drugs with higher molecular weight (such as venetoclax), tend to be slow crystallizers and can remain in the supersaturated state at the amorphous solubility across physiologically relevant time frames in the presence of amorphous drug-rich particles, which serve as reservoirs of absorbable drug.…”
Section: Introductionmentioning
confidence: 99%
“…It can be hypothesized, that by removing the drug-rich particles, the molecularly dispersed concentration dropped to the level of the crystalline solubility, as the increased chemical potential of the amorphous form was missing to maintain the amorphous solubility. In addition to progesterone, a similar study was also carried out with rifaximin, a P-gp substrate, and different polymers (Beig et al, 2017). The authors found that with increasing apparent solubility, the absorption rate constant in vivo only increased only after passing a certain solubility threshold.…”
Section: Mechanisms Of Uptake From Dissolved Asdsmentioning
confidence: 99%
“…An interplay between the 2 parameters determines whether the drug moiety will undergo absorption or not. [58][59][60][61][62] Knowing the range of Log p values where the drug is lipophilic enough, but still gets dissolved in the GIT is crucial for absorption. Hence, Log p or some other representation of lipophilicity is included in practically any drug absorption model.…”
Section: In Silico Model Settingsmentioning
confidence: 99%